(untitled) (Voice: A Biannual & Bilingual Journal, 2023)
This study investigated the speaking proficiency of bachelor level first year students who studied English Education at four affiliated campuses under the Facultuy of education (FoE), Tribhuvan University (TU). The data was collected from 40 students who were sampled using simple random sampling. The data was collected using oral test which examined eight aspects of speaking proficiency: accuracy, fluency, pronunciation, vocabulary, appropriateness, comprehension, confidence and body language. Oral test was also complemented by observation. The students’ speaking performance was scored and the scores were analyzed and interpreted using statistical and descriptive methods. The findings indicated that the students scored an average of 15.85% in speaking, with 55% below the average and 45% above. The study recommended various interventions, such as interventions like communication workshops, peerassisted learning, cultural sensitivity training, and interactive language exposure, to address the specific challenges and improve the overall speaking proficiency of the students. Furthermore, Multimodal instruction is proposed to boost pronunciation, vocabulary, appropriateness, and body language to improve speaking skill.